Nonredundant functions for tumor protein D52-like proteins support specific targeting of TPD52 - Shehata, M.; Bièche, I.; Boutros, R.; Weidenhofer, J.; Fanayan, S.; Spalding, L.; Zeps, Nikolajs; Byth, K.; Bright, R.; Lidereau, R.; Byrne, J. (American Association Cancer Research, 2008)
Purpose: Tumor protein D52 (TPD52 or D52) is frequently overexpressed in breast and other cancers and present at increased gene copy number. It is, however, unclear whether D52 amplification and overexpression target specific functional properties of the encoded protein. Experimental Design: The expression of D52-like genes and MAL2 was compared in breast tissues using quantitative reverse transcription-PCR.Thefunctions of human D52 and D53 genes were then compared by stable expression in BALB/c 3T3 fibroblasts and transient gene knockdown in breast carcinoma cell lines. In situ D52 and MAL2 protein expression was analyzed in breast tissue samples using tissue microarray sections. Results: The D52 (8q21.13), D54 (20q13.33), and MAL2 (8q24.12) genes were significantly overexpressed in breast cancer tissue (n = 95) relative to normal breast (n = l;P = 0.005) unlike the D53 gene (6q22.31; P = 0.884). Subsequently, D52-expressing but not D53-expressing 3T3 cell lines showed increased proliferation and anchorage-independent growth capacity, and reduced D52 but not D53 expression in SK-BR-3 cells significantly increased apoptosis. High D52 but not MAL2 expression was significantly associated with reduced overall survival in breast carcinoma patients (log-rank test, P < 0.001; n = 357) and was an independent predictor of survival (hazard ratio, 2.274; 95% confidence interval, 1.228-4.210; P = 0.009; n = 328). Conclusion: D52 overexpression in cancer reflects specific targeting and may contribute to a more proliferative, aggressive tumor phenotype in breast cancer. © 2008 American Association for Cancer Research.